Chitosan-based antimicrobial leather coatings : evaluation of the pilot scale production - Fernandes, I.P. (2011)
Chitosan is a biopolymer that is being increasingly used in distinct areas such as pharmaceutical, biomedical, cosmetics, food industry and agriculture. Among the interesting biological activities that have been ascribed to chitosan, the antimicrobial activity is probably the one that generates the higher number of applications. Considering that feet present favorable conditions for microorganism’s growth due to the high relative humidity conditions, warmth and nutrients availability (from feet sweat), one of such applications can be the use of chitosan to provide an antimicrobial coating for leather footwear components. Previous studies, in which leather impregnation with chitosan was performed at laboratory scale, showed that samples presented antimicrobial activity against Gram-positive and Gram-negative bacteria. In this work, the antimicrobial activity of chitosan-based leather coatings, produced at a pilot scale, was evaluated.